2002
DOI: 10.1053/joms.2002.29811
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and late mandibular fractures after third molar removal

Abstract: Purpose: In this retrospective study, we analyzed immediate and late mandibular fractures after impacted lower third molar surgery. Patients and Methods: One hundred fifty oral and maxillofacial surgeons in the north of-France were questioned about their experience with intraoperative and late mandibular fracture after third molar surgery. Cases were examined clinically and radiographically. Results: Thirty-seven fractures were reported in about 750,000 extractions (incidence of 0.0049%). Only 27 cases could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
20

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 8 publications
2
58
1
20
Order By: Relevance
“…After a reading of the articles had been performed for verification of the inclusion criteria, 11 articles were selected for the present review (Table 1). No literature reviews (14), mechanical assays with computer simulation (15), or metaanalyses (11) presenting a type of study or approach different from that evaluated in the present study (2,(16)(17)(18)(19)(20) and that did not define angle fracture (21) were selected. Among the articles selected, those presenting some type of sample limitation, for example, including a specific group of individuals (22,23), those not differentiating between erupted and absent third molars (24), and those including samples previously used in other studies (9,10,25) were excluded, with only studies remaining that clearly reported the data of the sample (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a reading of the articles had been performed for verification of the inclusion criteria, 11 articles were selected for the present review (Table 1). No literature reviews (14), mechanical assays with computer simulation (15), or metaanalyses (11) presenting a type of study or approach different from that evaluated in the present study (2,(16)(17)(18)(19)(20) and that did not define angle fracture (21) were selected. Among the articles selected, those presenting some type of sample limitation, for example, including a specific group of individuals (22,23), those not differentiating between erupted and absent third molars (24), and those including samples previously used in other studies (9,10,25) were excluded, with only studies remaining that clearly reported the data of the sample (8).…”
Section: Methodsmentioning
confidence: 99%
“…The mandible is the bone most susceptible to trauma in the facial region because of its more projected position in the facial skeleton (1)(2)(3), with an estimated frequency of 11.5 cases per 100,000 individuals/year. Individuals aged 16 to 30 years account for 50.2% of these fractures and mandibular angle fractures correspond to 40% of these cases.…”
Section: Introductionmentioning
confidence: 99%
“…Os benefícios advindos da remoção preventiva são superados pela elevada morbidade que o ato cirúrgico representa, devido a contraindicações relativas. Dentre elas, a idade do paciente, a condição médica comprometida e a proximidade ou contato com estruturas nobres 12 14 . Há uma diminuição das possibilidades de problemas associados aos dentes inclusos após o final da força de erupção, pois o elemento dentário tende a se fixar em uma posição.…”
Section: Figuraunclassified
“…Aus einer Umfrage unter Mund-, Kiefer-und Gesichtschirurgen in Frankreich ermittelten Libersa et al [17] auf der Basis von rund 750.000 Weisheitszahnentfernungen eine Inzidenz von Kieferwinkelfrakturen um 0,0049%. Das Verhältnis intraoperativer zu postoperativen Frakturen lag in etwa bei 3:2.…”
Section: Frakturen Durch Weisheitszahnentfernungunclassified